Comparative Performance of Two Different Biofertilizers in Acidic and Alkaline Soils on Okra Growth - Aysha Akter; Sonia Hossain (Journal of the Asiatic Society of Bangladesh, Science, 2025)
The present study evaluates the effects of two different types of biofertilizers on the growth of okra (Abelmoschus esculentus) following completely randomized design with three treatments (control, vermicompost, trichocompost) and three replications using acid soil (pH 4.77) and alkaline soil (pH 7.87) The results showed partial (pH 5.9) and complete (pH 6.4) neutralization of soil acidity by trichocompost and vermicompost whereas pH increased in alkaline soil but EC decreased significantly by both treatments. Besides, total OC, total N, total P, total K, total S all increased significantly (P <0.05) in both soils (except S in alkaline soil) by both biofertilizer application but total Ca, Mg, Fe, Mn decreased in acid soil while results were mixed in alkaline soil. Results of plant height and root length were increased significantly (p <0.01) in both acidic and alkaline soil by vermicompost and trichocompost application. For nutrient uptake, Vermicompost appeared equally useful for acidic and alkaline soil and trichocompost appeared more useful in acidic soil than alkaline soil. The application of the two biofertilizers in both the soils had significant positive effects on the growth of okra. J. Asiat. Soc. Bangladesh, Sci. 51(1): 103-114, June 2025